On the main factors affecting the imbalance of supply and demand in the market of educational services of higher education - Abdurayeva, G.E.; Torobekov, B.T. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The article is devoted to the problems of developing the training of transport and communication complex specialists and new approaches to solving this problem. Principles of formation of demand and supply in the market of educational services of higher education and labor market requirements to the professional level and the volume of highly skilled labor are given. The peculiarities of the transformation in the market of educational services of higher education are revealed through the formation of demand in the labor market for the preparation of a certain number and nomenclature of specialists in the necessary specialties and areas of university education. The reasons for the imbalance in the market of educational services of higher education and the labor market are analyzed. The tasks of the higher school are defined - which foresee the possibility of imbalance on the basis of studying the forecast of trends in demand and supply trends in the labor market and the market for higher education educational services and fulfill the role of a peculiar regulator in the interaction of these markets.
Жоғары білім беру қызметі нарығындағы сұраныстар мен ұсыныстардың тепе-теңдігіне əсер ететін негізгі факторлар туралы
Об основных факторах, влияющих на дисбаланс спроса и предложения на рынке образовательных услуг высшего образования
Keywords: graduates; education; services; labor market; specialty; qualification; entrant; highly skilled labor; vocational education; demand; supply; university system